-3(-7u+9)-6u=7(u-3)-4

Simple and best practice solution for -3(-7u+9)-6u=7(u-3)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-7u+9)-6u=7(u-3)-4 equation:


Simplifying
-3(-7u + 9) + -6u = 7(u + -3) + -4

Reorder the terms:
-3(9 + -7u) + -6u = 7(u + -3) + -4
(9 * -3 + -7u * -3) + -6u = 7(u + -3) + -4
(-27 + 21u) + -6u = 7(u + -3) + -4

Combine like terms: 21u + -6u = 15u
-27 + 15u = 7(u + -3) + -4

Reorder the terms:
-27 + 15u = 7(-3 + u) + -4
-27 + 15u = (-3 * 7 + u * 7) + -4
-27 + 15u = (-21 + 7u) + -4

Reorder the terms:
-27 + 15u = -21 + -4 + 7u

Combine like terms: -21 + -4 = -25
-27 + 15u = -25 + 7u

Solving
-27 + 15u = -25 + 7u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-7u' to each side of the equation.
-27 + 15u + -7u = -25 + 7u + -7u

Combine like terms: 15u + -7u = 8u
-27 + 8u = -25 + 7u + -7u

Combine like terms: 7u + -7u = 0
-27 + 8u = -25 + 0
-27 + 8u = -25

Add '27' to each side of the equation.
-27 + 27 + 8u = -25 + 27

Combine like terms: -27 + 27 = 0
0 + 8u = -25 + 27
8u = -25 + 27

Combine like terms: -25 + 27 = 2
8u = 2

Divide each side by '8'.
u = 0.25

Simplifying
u = 0.25

See similar equations:

| 319=c-253 | | 5(2x+3)=11x-(X-15) | | -2(t+2)+5*t=6*t+11 | | -x+1=5x-8 | | 2+4x-2x^2=2-2x | | 18x+24x+12x+6x=360 | | 16-b=15 | | 3x-7y-8x-y= | | 2x-6=6x+16 | | p+p=19-1 | | 5x+3y(5x*5y)=300 | | 5x+3y(5x*5y)=200 | | 5x+3y(5x*5y)=20 | | 7m+10=31 | | 6x-5=14x+25 | | 7t+7=21 | | 2(lnx^3)-lnx+3=7 | | 3x+6y=92 | | 3k+1=40 | | 7e+3=45 | | 2(9-6)+y=12 | | 4(x+9)=3(x-8)+x | | -2(t+2)+5*t=6t+11 | | 5s+17=157 | | 7h+4=7 | | 2.4=2+0.3x | | 7p^2+6=0 | | X-4x=231 | | 2cosx=x | | 4*(d-3)=2d | | 9x-2y=-18 | | 8x^3-28x+29=0 |

Equations solver categories